Arah Baru Pengembangan Ulumul Quran - mustain yusuf; Munawir Munawir (MAGHZA, 2019)
Muhkam science and mutasyabbih are the results of human construction. Its existence is clearly not absolutely true. As a science, muhkam and mutasyabbih are always open to all developments. This research - using Thomas Kuhn's shifting paradigm framework - analyzes the direction of the development of muhkam-mutasyabbih science starting from normal science, anomaly/crisis, and new paradigm. From this analysis, the answer is obtained that the construction of muhkam-mutasyabbih (normal science) is based on the textuality of the verse. This construction experiences anomaly and even crisis when dealing with maqashidul Qur'an, because by relying solely on verse textuality, there is often a counterproductive product between interpretation based on muhkam science and mutasyabbih with the maqashidul Qur'an itself. Here a new paradigm is born, value-based muhkam-mutasyabbih; muhkam is fundamental and universal values ​​(ushul Al-Qur'an), while mutasyabbih are implementational values ​​that are local-temporal (furu 'Al-Qur'an).